Effects of electrode configuration on MRR and EWR during electric discharge machining of Al/10wt%SiCp-MMC. (2016) - Kumar, Harmesh; Kumar, Rajesh; Manna, Alakesh
This paper reports the results of an experimental investigation carried out to study the effects of electrode shape along with size consideration on material removal rate (MRR) and electrode wear rate (EWR) during electric discharge machining of Al/10wt%SiCp-MMC. The RSM-based mathematical models of MRR and EWR are developed for different tool shapes such as circular, square and triangular using centre composites rotational design (CCD). Analysis of variance (ANOVA) has been performed to verify the fit and adequacy of the developed mathematical models. The percentage variation between the predicted and experimental values of the MRR and EWR during confirmation experiments have been found within 5%. The significant machining parameters have also been identified and their effects on responses such as MRR and EWR have been studied. The experimental results have shown that the best tool shape configuration for higher MRR and lower EWR is circular cross-section during electric discharge machining of Al/10wt%SiCp-MMC.